Low-wage work in the wealthy world - Gautié, Jérôme; Schmitt, John (Russell Sage Foundation, 2010)
"Low-Wage Work in the Wealthy World builds on an earlier Russell Sage Foundation study (Low-Wage America) to compare the plight of low-wage workers in the United States to five European countries - Denmark, France, Germany, the Netherlands, and the United Kingdom - where wage supports, worker protections, and social benefits have generally been stronger. By examining low-wage jobs in systematic case studies across five industries, this international study goes well beyond standard statistics to reveal national differences in the quality of low-wage work and the well-being of low-wage workers."--Jacket.